2010
DOI: 10.1111/j.1472-765x.2010.02915.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of sourdough lactic acid bacteria in commercial total mixed ration silage as revealed by denaturing gradient gel electrophoresis analysis

Abstract: Aims:  To characterize the bacterial communities in commercial total mixed ration (TMR) silage, which is known to have a long bunk life after silo opening. Methods and Results:  Samples were collected from four factories that produce TMR silage according to their own recipes. Three factories were sampled three times at 1‐month intervals during the summer to characterize the differences between factories; one factory was sampled 12 times, three samples each during the summer, autumn, winter and spring, to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…Because short‐term storage is preferable, the storage temperature during the ensiling process may remain low in winter products and high in summer products. In our survey of commercial products, the acetic acid content in TMR silage from warm conditions was higher than that in TMR silage from cold conditions, whereas the opposite trend was observed for ethanol content (Wang and Nishino ). Many studies have reported that hot conditions (35–40°C) can lower the lactic acid production and aerobic stability (Yokota et al .…”
Section: Introductionmentioning
confidence: 61%
“…Because short‐term storage is preferable, the storage temperature during the ensiling process may remain low in winter products and high in summer products. In our survey of commercial products, the acetic acid content in TMR silage from warm conditions was higher than that in TMR silage from cold conditions, whereas the opposite trend was observed for ethanol content (Wang and Nishino ). Many studies have reported that hot conditions (35–40°C) can lower the lactic acid production and aerobic stability (Yokota et al .…”
Section: Introductionmentioning
confidence: 61%
“…Adesogan et al (2003) reported that inoculating the species of L. fermentum alone has less effect than when it is combined with other species. Wang & Nishino (2010) concluded that L. fermentum was predominant in nonensiled material, while L. brevis and L. buchneri became prevalent during the fermentation process. Tjandraatmadja et al (1994) found significant quantities of L. fermentum in Panicum maximum cv.…”
Section: Resultsmentioning
confidence: 99%
“…In natural fermentation, ALAB can increase the availability of carbohydrates that have been rapidly fermented by partial hydrolysis of starch, provided that their α-amylase is able to hydrolyze these granules (Rodriguez Sanoja et al, 2000). The association of L. fermentum with L. buchneri increased the aerobic stability of silage with high humidity (Wang & Nishino, 2010). Adesogan et al (2003) reported that inoculating the species of L. fermentum alone has less effect than when it is combined with other species.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were sent to the laboratory in refrigerated containers and preserved at −70°C until analysis. The fecal samples were analyzed by an equipped laboratory (Cell Biotech Co., Ltd., Seoul, Korea) using DGGE and RT-PCR [25]. The detailed methods of DGGE and RT-PCR used in this trial were described briefly elsewhere [11].…”
Section: Methodsmentioning
confidence: 99%